Clinical Genealogical and Epigenetic Examination of Patients with Juvenile Epiphysiolysis of the Femoral Head - Holiuk, Ye.L.; Kabatsii, M.S.; Filipchuk, V.V.; Melnyk, M.V.; Lukianova, N.Yu. (TERRA ORTHOPAEDICA, 2021)
Summary. Slipped capital femoral epiphysis (SCFE) is a multifactorial disease caused by a number of factors, and each of them can be triggered in its occurrence. Modern research is increasingly pointing to the leading role of epigenetic structures in the origin and course of this group of diseases. In recent years, the most promising area is the study of the role of microRNAs as an epigenetic factor that plays a leading role in the pathogenesis of multifactorial diseases. Objective: to develop a methodology for genetic genealogical examination of patients with juvenile epiphysiolysis of the femoral head. Materials and Methods. The study material was 26 patients with SCFE (15 girls and 11 boys) in different periods of sexual development: prepuberty – 7 patients, induction of puberty – 12 patients, and puberty and postpuberty – 7 patients. A questionnaire developed by us was used for clinical and genealogical research of the patients. The material for the epigenetic study, namely the study of microRNA-21 expression in patients with SCFE, was venous blood. Results. The expression of microRNA-21 in the blood of patients with SCFE is different (average expression is 0.86 conventional units) from those of healthy donors (average 0.393 conventional units) of the same age (p<0.05). Analysis of dependence on the period of sexual development revealed statistical differences in indicators depending on the group (p<0.05). No dependence of the level of microRNA-21 expression in patients with SCFE on sex and the period before or after surgery (p>0.05) was revealed. The obtained data on the probability of the influence of hereditary factors on the occurrence of SCFE are statistically significant (p<0.05). Conclusions. Our results of epigenetic and clinical genealogical research of patients with SCFE showed a high probability of influence of hereditary and epigenetic factors on the occurrence and course of this disease.